Assessment of currently used organochlorine pesticides in surface water and sediments in Xiangjiang river, a drinking water source in China: Occurrence and distribution characteristics under flood events. (1st July 2022) - Zhang, Shengwei; Zhao, Wenyu; Yang, Chao; Li, Yanxia; Liu, Mengyue; Meng, Xiang−Zhou; Cai, MingHong
Abstract: Xiangjiang (XJ) is a typical urban inland river that serves as a drinking water source, which may be affected by the currently used organochlorine pesticides (CUOCPs) originating from agricultural activities in the vicinity. On this basis, this study comprehensively explored the occurrence and distribution characteristics of CUOCPs in surface water and sediments under long-term precipitation and subsequent floods. Considering the low concentration of CUOCPs in water, a technique combining high-throughput organic analysis with high-volume solid phase extraction (High-throat/Hi-volume SPE) was introduced for effective analysis of CUCOPs. The results showed that the concentration of CUOCPs in the water and sediments of XJ ranged from 2.33 to 6.40 ng L −1 (average of 3.93 ± 1.15 ng L −1 ) and from 1.52 to 21.2 ng g −1 (average of 6.60 ± 4.31 ng g −1 dw), respectively. The distribution of CUOCPs in water was consistent throughout XJ, but that in sediments was not uniform, indicating a stronger impact of floods on water than on sediments. Water-sediment partition coefficients were generally >2 L g −1, showing a tendency of CUOCP dominance in sediments. The results of principal component analysis and cluster analysis showed that the occurrence of CUOCPs is significantly affected by exogenous disturbance, which could be flood events; meanwhile, clusters of CUOCPs were found in both water and sediments in the source-limited middle reaches in urban areas. Redundancy analysis (RDA) showed that CUOCP occurrences were not positively correlated with nutrient elements (nitrogen and phosphorus), but related to pH and dissolved oxygen (DO), indicating complex sources. Graphical abstract: Image 1 Highlights: Currently used organochlorine pesticides (CUOCPs) in water and sediment were studied. Low-level CUOCPs in river and tap water from Xiangjiang were obtained. CUOCPs are more enriched in sediments than in river water. Flood events have stronger influence on river water than on sediments.